Penyusunan Laporan Keuangan Masjid Agung Sibolga Berdasarkan ISAK No. 335 - Yolanda Aulia Rahma Sitorus; Rini Elvira; Yuwarman Mansur (Program Studi Ekonomi Islam - UIN Sjech M. Djamil Djambek Bukttinggi, 2025)
Socio-cultural and economic developments drive non-profit organizations, including mosques, to adapt toward more accountable and transparent financial management. As entities managing public funds from zakat, infaq, alms, and donations, mosques require clear accountability to the community. This research aims to analyze the preparation of financial reports at Masjid Agung Sibolga based on the Interpretation of Financial Accounting Standards (ISAK) No. 35, utilizing the perspectives of accountability theory and legitimacy theory. The study employs a descriptive qualitative approach through a case study method, collecting data via transaction documentation, existing financial reports, and interviews with mosque administrators. Data processing involved creating a chart of accounts, recording transactions in general journals, and compiling financial statements using Accurate accounting software. These stages were adjusted to meet the non-profit reporting principles regulated in ISAK No. 35. The results indicate that the financial management of Masjid Agung Sibolga still relies on conventional methods, which do not yet align with standard non-profit financial reporting requirements. Through adjustments based on ISAK No. 35, the mosque's financial reports were structured to include a statement of financial position, statement of activities, statement of changes in net assets, cash flow statement, and notes to the financial statements. Analysis of the income statement revealed an operational deficit, reflecting a gap between revenue and operational expenses. The findings demonstrate that implementing ISAK No. 35 not only improves financial reporting quality but also enhances the accountability of mosque management and strengthens public trust in the mosque's financial governance.